Pendampingan Penerapan Teknologi Pasteurisasi dan Diversifikasi Produk Susu Kambing di Desa Dlemer Bangkalan - Nurmalisa Lisdayana; Sheilla Aprilia Nur Nadhifah; Ferbieko Naio Widodo; Raden Faridz; Eka Nurrahema Ning Asih; Iffan Maflahah (Lembaga Pengembangan Kinerja Dosen, 2026)
The Alvina Jaya Farmers Group in Dlemer Village, Arosbaya District, Bangkalan Regency, has significant potential in goat farming, particularly in milk production. However, the pasteurized goat milk production process still faces various obstacles, such as manual milking that is prone to contamination, traditional pasteurization using boilers that make it difficult to maintain temperature stability, simple packaging without labels, and limited marketing. Through the 2025 community service program at Trunojoyo University in Madura, assistance was provided in the implementation of modern technology in the form of automatic milking machines, pasteurization machines, and the development of labeled packaging. In addition, diversification of derivative products in the form of goat milk yogurt was also introduced. The results of the activity showed an increase in productivity, hygiene, and product shelf life, accompanied by an increase in the skills of farmer group members in production and digital marketing. The diversification of yogurt products also opened up new business opportunities with higher added value. This program not only increased the income of farmer groups but also had a social impact by providing nutritious products that are safe for public consumption.